Fast-charging multilayer composite solid electrolyte, preparation method and application

By designing a multi-layer composite solid electrolyte in an all-solid-state lithium-ion battery, combining high-ion conductive electrolytes and lithium dendrites with LiBH4-based electrolytes, the problem that solid electrolytes in the prior art is difficult to take into account high ionic conductivity and high critical current density, and the battery's high energy density, cycle stability and rate performance are improved.

CN119581648APending Publication Date: 2025-03-07RES INST OF ZHEJIANG UNIV TAIZHOU +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411196269.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-08-26
Filing Date
2024-08-29
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

It is difficult for existing solid electrolytes to take into account high ion conductivity and high critical current density in lithium-ion batteries, resulting in limited energy density, cycling stability and rate performance.

Method used

A multi-layer composite solid electrolyte is designed, using a high ionic conductive electrolyte as the intermediate layer, and a LiBH4-based composite solid electrolyte with strong lithium dendrite resistance is added to both sides. This structure achieves both high ionic conductivity and high critical current density.

Benefits of technology

It has achieved stable circulation of all-solid-state lithium-ion batteries at high magnifications, with huge practical potential and can meet the needs of fast charging and discharging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581648A_ABST
    Figure CN119581648A_ABST
Patent Text Reader

Abstract

The invention discloses a fast-charging multi-layer composite solid electrolyte, a preparation method and application, the fast-charging multi-layer composite solid electrolyte is designed and constructed, the middle layer is a solid electrolyte with high ionic conductivity, and the two sides are LiBH4-based composite solid electrolytes with high critical current density; the problem that the ionic conductivity and the critical current density of single sulfide, halide, oxide and borohydride are difficult to consider at the same time is solved, the multi-layer composite solid electrolyte has high ionic conductivity and high critical current density at the same time, and the breakthrough of the comprehensive performance of the composite solid electrolyte is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of all-solid-state batteries, and specifically relates to a fast-chargeable multi-layer composite solid electrolyte, a preparation method and an application thereof. Background Art

[0002] Lithium-ion batteries have been widely used in electric vehicles, consumer electronics, and large-scale energy storage. However, commercial lithium-ion batteries currently use flammable organic solvents as electrolytes, which pose potential safety risks. In addition, due to the electrochemical stability of the electrolyte, it is difficult to match lithium metal negative electrode materials with higher specific capacity and high-voltage positive electrode materials. The energy density of traditional lithium-ion batteries tends to the theoretical limit and cannot meet the rapidly growing demand for high-energy-density energy storage and long-range electric vehicles.

[0003] In comparison, all-solid-state batteries use solid electrolytes to replace existing electrolytes, fundamentally avoiding the use of flammable organic solvents and achieving the intrinsic safety of lithium-ion batteries. In addition, solid electrolytes can match positive and negative electrode materials with higher specific capacity, breaking through the bottleneck of mass and volume energy density of current liquid lithium-ion batteries. However, the ion transport kinetics, high voltage compatibility and electrochemical stability of single oxide, halide, sulfide, polymer and borohydride solid electrolytes are currently deficient, and the ion conductivity and critical current density cannot meet the requirements of stable cycling of high energy density lithium-ion batteries. Among them, solid electrolytes such as chlorides and sulfides have high ion conductivity, but poor stability to lithium, weak resistance to dendrite growth, low critical current density, and are prone to forming a large number of lithium dendrites when charging and discharging at high battery rates, piercing the electrolyte membrane and causing short circuits; borohydride-based electrolytes have good stability to lithium and high critical current density, but low room temperature ion conductivity. The defects of these electrolytes make it difficult to meet the needs of fast charging and discharging of all-solid-state batteries.

[0004] Therefore, in order to solve the current problem that the lithium ion conductivity and critical current density of solid electrolytes cannot be taken into account at the same time, it is urgently necessary to provide a composite solid electrolyte with both high ionic conductivity and high critical current density to achieve breakthroughs in the energy density, cycle stability and rate performance of all-solid-state lithium-ion batteries. Summary of the invention

[0005] The present invention provides a fast-chargeable multilayer composite solid electrolyte, a preparation method and an application thereof. The present invention can obtain a solid electrolyte having a high critical current density and high ionic conductivity at room temperature.

[0006] The present invention provides a fast-charging multilayer composite solid electrolyte, the electrolyte material having a three-layer structure, including an intermediate layer of a high ion conductivity electrolyte and composite layers of a high critical current density electrolyte located on both sides of the intermediate layer, including the following features:

[0007] (1) The middle layer of the composite electrolyte is a high ionic conductivity electrolyte;

[0008] (2) Both sides of the composite electrolyte are high critical current density solid electrolytes;

[0009] The fast-chargeable multi-layer composite solid electrolyte described in the present invention has composite layers on both sides that are solid electrolytes with strong resistance to lithium dendrites, which inhibit the formation and growth of dendrites under high-rate current density, and the middle layer is a solid electrolyte with high ionic conductivity, which improves the lithium ion transport kinetics of the electrolyte. This multi-layer structure design constructs a composite solid electrolyte that can achieve both high ionic conductivity and high critical current density.

[0010] In feature (1), the high ionic conductivity electrolyte intermediate layer is one or more of an oxide electrolyte, a halide electrolyte or a sulfide electrolyte;

[0011] The oxide electrolyte includes a garnet-type solid electrolyte and a composite solid electrolyte thereof. The garnet-type solid electrolyte is composed of Li 7-x A y La 3-y Zr 2-x M x O 12 (wherein A is one of Mg, Ca, S, Ba, Nb, and Ta; M is one of Ta, Nb, Hf, Al, Si, Ga, Ge, Sc, Ti, V, Y, and Sn, 0≤x≤1, 0≤y≤1);

[0012] The halide electrolyte includes Li 3-n D 1-n Zr n X6 (wherein D is one of Y, Er, In; X is Cl or Br, 0≤n≤1) and modified solid electrolytes thereof;

[0013] The sulfide electrolyte includes Li3PS4, Li7P3S 11 , Li 10 GeP2S 12 , Li (6-i) PS (5-i) E (1+i) (wherein E is one of Cl, Br, I, 0≤i≤0.6), jLi2S·(1-j)P2S5(0.2≤j≤0.8) and modified electrolytes thereof;

[0014] Furthermore, the oxide electrolyte is Li 6.4 Ln3Z 1.4 Ta 0.6 O 12The composite electrolyte of (LLZTO) and LiBH4 is LLZTO-4LiBH4; the halide electrolyte is Li3InCl6; and the sulfide electrolyte is Li6PS5Cl.

[0015] In feature (2), the composite LiBH4-based solid electrolyte includes one or more of LiBH4-ZrCl4, LiBH4-TiCl4, LiBH4-ZrI4, LiBH4-TiI4, LiBH4-HfCl4, LiBH4-HfI4, LiBH4-YCl4, LiBH4-TaCl5, and LiBH4-LaCl3.

[0016] The present invention also provides a method for preparing a fast-chargeable multilayer composite solid electrolyte. Studies have shown that the fast-chargeable multilayer composite solid electrolyte prepared according to the method of the present invention has a critical current density of up to 15.2 mA / cm at room temperature. 2 The multilayer composite material prepared by the present invention is used as an electrolyte sheet, LiCoO2 or TiS2 is used as a positive electrode, and lithium metal is used as a negative electrode material. The assembled all-solid-state lithium-ion battery has a stable cycle at a high rate and has great practical potential. The preparation method includes the following steps:

[0017] Step 1: In an argon atmosphere glove box, weigh a certain amount of high ionic conductivity electrolyte powder into a stainless steel mold, and use a hydraulic press or a roller press to press the powder into a high ionic conductivity electrolyte sheet;

[0018] Step 2: Weigh a certain amount of high critical current density solid electrolyte powder and compound it on both sides of the high ion conductivity electrolyte sheet to form a sandwich-type multi-layer composite solid electrolyte sheet.

[0019] Furthermore, the pressure of the hydraulic press or roller press acting on the electrolyte intermediate layer is 60-125 MPa.

[0020] Furthermore, the pressure of the hydraulic press or roller press acting on the electrolyte intermediate layer is 125 MPa.

[0021] Furthermore, the mass ratio of the high ionic conductivity electrolyte powder to the high critical current density solid electrolyte powder is m:1-m, wherein 0 <m<1。

[0022] Furthermore, the mass ratio of the high ionic conductivity electrolyte powder to the high critical current density solid electrolyte powder is 8:2.

[0023] The composite method in step 2 is: placing a quantitative high critical current density solid electrolyte powder on both sides of the high ion conductivity electrolyte sheet, and pressing with a hydraulic press or a roller press to form a sandwich-type multi-layer composite solid electrolyte sheet;

[0024] Further, the pressure exerted by the hydraulic press or roll press on the sandwich - type multi - layer composite solid electrolyte sheet is 150 - 450 MPa.

[0025] Further, the pressure exerted by the hydraulic press or roll press on the sandwich - type multi - layer composite solid electrolyte sheet is 375 MPa.

[0026] Alternatively, the composite method in step 2 is to in - situ polymerize a quantitative high - critical - current - density solid electrolyte powder on both sides of a high - ionic - conductivity electrolyte sheet. The in - situ polymerization includes dispersing and mixing an electrolyte, a small - molecule monomer, a binder, and a polymerization initiator in a solvent in a set ratio to form a slurry, coating the slurry on both sides of the high - ionic - conductivity electrolyte sheet, drying to remove the solvent, and promoting the polymerization of the small - molecule monomer to form an organic - inorganic composite electrolyte layer.

[0027] Further, the small - molecule monomer used in the in - situ polymerization includes one or a mixture of two or more of ethoxylated trimethylolpropane triacrylate, cyclic carbonate, vinylene carbonate, diallyl carbonate, ethylene glycol dimethacrylate, ethylene sulfite vinyl ester, fluoro vinylene carbonate, vinyl acetate, 1,3 - propylene - sulfonic acid lactone, ethylene ethyl carbonate, maleimide compounds, maleamide compounds, maleic anhydride compounds, methyl vinyl sulfone, ethyl vinyl sulfone, methyl methacrylate, butyl acrylate, and acrylamide.

[0028] Further, the small - molecule monomer used in the in - situ polymerization is cyclic carbonate.

[0029] On the other hand, the present invention also provides an application of the fast - chargeable multi - layer composite solid electrolyte in a all - solid - state lithium - ion battery, assembling the fast - chargeable multi - layer composite solid electrolyte with a positive electrode material and a negative electrode material into an all - solid - state battery.

[0030] Preferably, the positive electrode material is TiS2, LiCoO2, LiNi 1-a-t Co a Mn t O2(0 < a < 0.5, 0 < t < 0.5, NCM), LiNi 1-e-w Co e Al w O2(0 < e < 0.5, 0 < w < 0.5, NCA), LiMn2O4, LiNi 0.5 Mn 1.5 O4, LiFePO4, zLi2MnO3·(1 - z)LiRO2 (where 0 < z < 1, R is a transition metal); the negative electrode material is a lithium metal negative electrode or a silicon - based negative electrode.

[0031] Compared with the prior art, the beneficial effects of the present invention are:

[0032] The present invention designs and constructs a fast-charging multi-layer composite solid electrolyte, in which the middle layer is a solid electrolyte with high ionic conductivity, and the two sides are LiBH4-based composite solid electrolytes with high critical current density. This solves the problem that it is difficult to take both the ionic conductivity and critical current density of single sulfide, halide, oxide and borohydride into account. The multi-layer composite solid electrolyte has both high ionic conductivity and high critical current density, achieving a breakthrough in the comprehensive performance of the composite solid electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 Schematic diagram of the structure of the fast-chargeable multilayer composite solid electrolyte prepared in Example 1 and Comparative Example 1 of the present invention.

[0034] Figure 2 This is a critical current density (CCD) test curve of the fast-chargeable multilayer composite solid electrolyte 22LiBH4-ZrCl4|Li3InCl6|22LiBH4-ZrCl4 prepared in Example 1 of the present invention.

[0035] Figure 3 This is a critical current density (CCD) test curve of the multilayer composite solid electrolyte Li3InCl6|22LiBH4-ZrCl4|Li3InCl6 prepared in Comparative Example 1 of the present invention.

[0036] Figure 4 Electrochemical impedance spectroscopy (EIS) spectra of the fast-chargeable multilayer composite solid electrolyte 22LiBH4-ZrCl4|Li3InCl6|22LiBH4-ZrCl4 prepared in Example 1 of the present invention and Li3InCl6|22LiBH4-ZrCl4|Li3InCl6 of Comparative Example 1.

[0037] Figure 5 This is a direct current polarization (DC) curve diagram of the fast-chargeable multilayer composite solid electrolyte 22LiBH4-ZrCl4|Li3InCl6|22LiBH4-ZrCl4 prepared in Example 1 of the present invention and Li3InCl6|22LiBH4-ZrCl4|Li3InCl6 of Comparative Example 1.

[0038] Figure 6 Schematic diagram of the structure of the multilayer composite solid electrolyte prepared in Example 2 of the present invention and Comparative Example 2.

[0039] Figure 7 This is a critical current density (CCD) test curve of the fast-chargeable multilayer composite solid electrolyte 22LiBH4-ZrCl4|LLZTO-4LiBH4|22LiBH4-ZrCl4 prepared in Example 2 of the present invention.

[0040] Figure 8 This is a critical current density (CCD) test curve of the multilayer composite solid electrolyte LLZTO-4LiBH4|22LiBH4-ZrCl4|LLZTO-4LiBH4 prepared in Comparative Example 2 of the present invention.

[0041] Fig. 9 Electrochemical impedance spectroscopy (EIS) spectra of the fast-chargeable multilayer composite solid electrolyte 22LiBH4-ZrCl4|LLZTO-4LiBH4|22LiBH4-ZrCl4 prepared in Example 2 of the present invention and LLZTO-4LiBH4|22LiBH4-ZrCl4|LLZTO-4LiBH4 of Comparative Example 2.

[0042] Fig.10 This is a direct current polarization (DC) curve diagram of the fast-chargeable multilayer composite solid electrolyte 22LiBH4-ZrCl4|LLZTO-4LiBH4|22LiBH4-ZrCl4 prepared in Example 2 of the present invention and LLZTO-4LiBH4|22LiBH4-ZrCl4|LLZTO-4LiBH4 of Comparative Example 2.

[0043] Fig.11 This is a critical current density (CCD) test curve of the composite solid electrolyte LLZTO-22LiBH4-ZrCl4 prepared in Comparative Example 11 of the present invention.

[0044] Fig.12 This is the electrochemical impedance spectroscopy (EIS) spectrum of the composite solid electrolyte LLZTO-22LiBH4-ZrCl4 prepared in Comparative Example 11 of the present invention.

[0045] Fig.13 This is a critical current density (CCD) test curve of the composite solid electrolyte Li3InCl6-22LiBH4-ZrCl4 prepared in Comparative Example 12 of the present invention.

[0046] Fig.14 This is the electrochemical impedance spectroscopy (EIS) spectrum of the composite solid electrolyte Li3InCl6-22LiBH4-ZrCl4 prepared in Comparative Example 12 of the present invention.

[0047] Fig.15 This is a cycle performance diagram of the all-solid-state battery assembled in Application Example 1 of the present invention. DETAILED DESCRIPTION

[0048] The present invention is further described below with reference to the examples, but the scope of the present invention is not limited thereto. The materials involved in the examples are all commercially available products.

[0049] Example 1

[0050] In an argon atmosphere glove box, 80 mg of electrolyte Li3InCl6 powder was weighed and placed in a stainless steel mold with a diameter of 10 mm, and then the electrolyte powder was pressed into a sheet using a hydraulic press at a pressure of 125 MPa. Then 10 mg of electrolyte 22LiBH4-ZrCl4 powder was weighed and placed on the upper and lower sides of the Li3InCl6 electrolyte sheet, and the whole was pressed into a sandwich-type electrolyte sheet using a hydraulic press at a pressure of 375 MPa to obtain a fast-charging multi-layer composite solid electrolyte, recorded as 22LiBH4-ZrCl4|Li3InCl6|22LiBH4-ZrCl4.

[0051] Example 2

[0052] In an argon atmosphere glove box, 80 mg of electrolyte LLZTO-4LiBH4 powder was weighed and placed in a stainless steel mold with a diameter of 10 mm, and then the electrolyte powder was pressed into a sheet using a hydraulic press at a pressure of 125 MPa. Then 10 mg of electrolyte 22LiBH4-ZrCl4 powder was weighed and placed on the upper and lower sides of the LLZTO-4LiBH4 electrolyte sheet, and the whole was pressed into a sandwich-type electrolyte sheet using a hydraulic press at a pressure of 375 MPa to obtain a fast-charging multilayer composite solid electrolyte, recorded as 22LiBH4-ZrCl4|LLZTO-4LiBH4|22LiBH4-ZrCl4.

[0053] Embodiment 3-4

[0054] Different from Example 1, the pressures of the hydraulic presses in Examples 3-4 are different, and the pressures of the obtained sandwich electrolyte sheets in the hydraulic presses are set to 200 MPa and 250 MPa, respectively.

[0055] Embodiment 5-6

[0056] Different from Example 2, the pressures of the hydraulic presses in Examples 5-6 are different, and the pressures of the obtained sandwich electrolyte sheets in the hydraulic presses are set to 200 MPa and 250 MPa, respectively.

[0057] Embodiment 7-8

[0058] Different from Example 1, the mass ratio of Li3InCl6 and 22LiBH4-ZrCl4 in Examples 7-8 is different, and the weighed masses of Li3InCl6 and 22LiBH4-ZrCl4 are 60 mg and 20 mg respectively.

[0059] Examples 9-10

[0060] Different from Example 2, the mass ratios of LLZTO-4LiBH4 and 22LiBH4-ZrCl4 in Examples 9-10 are different, and the weighed masses of LLZTO-4LiBH4 and 22LiBH4-ZrCl4 are 60 mg and 20 mg, respectively.

[0061] Comparative Example 1

[0062] In an argon atmosphere glove box, 80 mg of electrolyte 22LiBH4-ZrCl4 powder was weighed and placed in a stainless steel mold with a diameter of 10 mm, and then the electrolyte powder was pressed into a sheet using a hydraulic press at a pressure of 125 MPa. Then 10 mg of electrolyte Li3InCl6 powder was weighed and placed on the upper and lower sides of the 22LiBH4-ZrCl4 electrolyte sheet, and the whole was pressed into a sandwich-type electrolyte sheet using a hydraulic press at a pressure of 375 MPa to obtain a multilayer composite solid electrolyte, recorded as Li3InCl6|22LiBH4-ZrCl4|Li3InCl6.

[0063] Comparative Example 2

[0064] In an argon atmosphere glove box, 80 mg of electrolyte 22LiBH4-ZrCl4 powder was weighed and placed in a stainless steel mold with a diameter of 10 mm, and then the electrolyte powder was pressed into a sheet using a hydraulic press at a pressure of 125 MPa. Then 10 mg of electrolyte LLZTO-4LiBH4 powder was weighed and placed on the upper and lower sides of the 22LiBH4-ZrCl4 electrolyte sheet, and the whole was pressed into a sandwich-type electrolyte sheet using a hydraulic press at a pressure of 375 MPa to obtain a multilayer composite solid electrolyte, recorded as LLZTO-4LiBH4|22LiBH4-ZrCl4|LLZTO-4LiBH4.

[0065] Comparative Examples 3-4

[0066] Different from Comparative Example 1, the pressure of the hydraulic press in Comparative Examples 3-4 is different, and the pressure of the obtained sandwich electrolyte sheet in the hydraulic press is set to 200 MPa or 250 MPa.

[0067] Comparative Examples 5-6

[0068] Different from Comparative Example 2, the pressure of the hydraulic press in Comparative Examples 5-6 is different, and the pressure of the obtained sandwich electrolyte sheet in the hydraulic press is set to 200 MPa or 250 MPa.

[0069] Comparative Examples 7-8

[0070] Different from Comparative Example 1, the mass ratio of 22LiBH4-ZrCl4 and Li3InCl6 in Comparative Examples 7-8 is different, and the weighed masses of 22LiBH4-ZrCl4 and Li3InCl6 are 60 mg and 20 mg respectively.

[0071] Comparative Examples 9-10

[0072] Different from Comparative Example 2, the mass ratios of 22LiBH4-ZrCl4 and LLZTO-4LiBH4 in Comparative Examples 9-10 are different, and the weighed masses of 22LiBH4-ZrCl4 and LLZTO-4LiBH4 are 60 mg and 20 mg, respectively.

[0073] Comparative Example 11

[0074] In an argon atmosphere glove box, 20 mg of electrolyte 22LiBH4-ZrCl4 powder and 80 mg of electrolyte LLZTO-4LiBH4 powder were weighed, ground and mixed evenly, placed in a stainless steel mold with a diameter of 10 mm, and then pressed into a sandwich-type electrolyte sheet using a hydraulic press at a pressure of 375 MPa to obtain a composite solid electrolyte, recorded as LLZTO-22LiBH4-ZrCl4.

[0075] Comparative Example 12

[0076] In an argon atmosphere glove box, 20 mg of electrolyte 22LiBH4-ZrCl4 powder and 80 mg of electrolyte Li3InCl6 powder were weighed, ground and mixed evenly, placed in a stainless steel mold with a diameter of 10 mm, and then pressed into a sandwich-type electrolyte sheet using a hydraulic press at a pressure of 375 MPa to obtain a composite solid electrolyte, recorded as Li3InCl6-22LiBH4-ZrCl4.

[0077] like Figure 1 As shown, the chemical composition of the fast-chargeable multilayer composite solid electrolyte prepared in Example 1 and Comparative Example 1 is the same, the positions of the intermediate layer and the composite layer are opposite, and the substantial difference between the two is that the composite layers located on both sides have good stability to lithium, strong resistance to dendrite formation, and high critical current density. The sandwich electrolyte structure design of Example 1 can obtain a composite electrolyte with high ionic conductivity and high critical current density.

[0078] like Figure 2 As shown in FIG. 1 , the critical current density (CCD) test curve of the multilayer composite solid electrolyte 22LiBH4-ZrCl4|Li3InCl6|22LiBH4-ZrCl4 prepared in Example 1 is shown. At room temperature 25°C, the critical current density of the composite electrolyte reaches 4.5 mA / cm 2The critical current density is used to evaluate the ability of solid electrolytes to inhibit lithium dendrites and is defined as the current density that enables lithium dendrites to grow through SEI and solid electrolyte and short-circuit the battery. The high critical current density of the multilayer composite solid electrolyte of Example 1 indicates that the material has good stability to lithium, which is mainly due to the excellent anti-dendrite generation ability of the borohydride-based electrolyte.

[0079] like Figure 3 As shown in Figure 1, the critical current density (CCD) test curve of the fast-chargeable multilayer composite solid electrolyte Li3InCl6|22LiBH4-ZrCl4|Li3InCl6 prepared in Comparative Example 1. At room temperature 25°C, the critical current density of the composite electrolyte is less than 0.1 mA / cm 2 The halides on both sides of the composite electrolyte do not have a high critical current density because the critical current density of the halide electrolyte itself is low, the interfaces on both sides of the composite electrolyte have poor lithium stability, and weak resistance to dendrite formation, which cannot meet the requirements of high-rate charge and discharge of all-solid-state batteries.

[0080] like Figure 4 As shown, it is the electrochemical impedance spectrum (EIS) of the composite electrolyte material 22LiBH4-ZrCl4|Li3InCl6|22LiBH4-ZrCl4 prepared in Example 1 and Li3InCl6|22LiBH4-ZrCl4|Li3InCl6 prepared in Comparative Example 1. Due to the rapid lithium ion conductivity of this type of material, only one straight line is finally presented in the EIS graph. According to the spectrum, at 30°C, the impedance of 22LiBH4-ZrCl4|Li3InCl6|22LiBH4-ZrCl4 is R=291Ω, and the impedance of Li3InCl6|22LiBH4-ZrCl4|Li3InCl6 is R=267Ω. According to the formula σ Li+ =d / SR, the calculated lithium ion conductivity is 4.375×10 -4 S / cm and 4.768×10 -4 S / cm. There is no significant difference in the ionic conductivity of the two. Placing the lithium-stable borohydride-based electrolyte on both sides achieves high ionic conductivity without significantly reducing the conductivity of the composite solid electrolyte. The ionic conductivity is related to the composition and phase structure of the solid electrolyte. Both are composed of two electrolytes with the same overall composition but different composite methods. This shows that in the form of a sandwich-type multi-layer composite solid electrolyte sheet, the positions of the middle layer and the composite layer are opposite, which does not significantly affect the overall lithium ion transmission rate.

[0081] like Figure 5As shown in the figure, the DC polarization curves (DC) of the composite electrolyte material 22LiBH4-ZrCl4|Li3InCl6|22LiBH4-ZrCl4 prepared in Example 1 and Li3InCl6|22LiBH4-ZrCl4|Li3InCl6 prepared in Comparative Example 1, at 30°C, the measured voltage U0=0.1V, and the final steady-state current I0 are 2.18×10 -8 A and 2.76×10 -8 A, according to the electronic conductivity calculation formula σ e- =I0d / U0S, the final calculation can get the electronic conductivity σ e -7.028×10 -8 S / cm and 5.551×10 -8 S / cm, which is 5 orders of magnitude smaller than the ionic conductivity and can be ignored. The electronic conductivity of the composite electrolytes of Example 1 and Comparative Example 1 is close, indicating that different combinations of electrolyte layers have no significant effect on their electronic conductivity and can meet the application requirements of solid electrolytes.

[0082] like Figure 6 As shown, the fast-charging multilayer composite solid electrolyte prepared in Example 2 and Comparative Example 2 has the same chemical composition, and the middle layer and the composite layer are opposite. The composite electrolyte with high ionic conductivity and high critical current density is obtained by designing this sandwich-type multilayer composite solid electrolyte sheet. The middle layer of Example 1 adopts a halide electrolyte with high ionic conductivity, while the middle layer of Example 2 adopts an oxide electrolyte. At present, the solid electrolytes of different all-solid-state batteries have their own advantages and disadvantages. Example 1 and Example 2 respectively use halide and oxide electrolytes with high ionic conductivity as the middle layer, indicating the universality and versatility of this technical method.

[0083] like Figure 7 As shown in Figure 2, the critical current density (CCD) test curve of the fast-chargeable multilayer composite solid electrolyte 22LiBH4-ZrCl4|LLZTO-4LiBH4|22LiBH4-ZrCl4 prepared in Example 2. At room temperature of 25°C, the critical current density of the composite electrolyte reaches 15.2 mA / cm 2 , indicating that the material has good stability to lithium.

[0084] like Figure 8 As shown in Figure 2, the critical current density (CCD) test curve of the fast-chargeable multilayer composite solid electrolyte LLZTO-4LiBH4|22LiBH4-ZrCl4|LLZTO-4LiBH4 prepared in Comparative Example 2. At room temperature 25°C, the critical current density of the composite electrolyte is less than 2.35 mA / cm 2, indicating that oxide-based electrolytes have poor stability to lithium and their surfaces are in contact with lithium metal, making it impossible to achieve a high critical current density.

[0085] like Fig. 9 As shown, it is the electrochemical impedance spectrum (EIS) of the composite electrolyte material 22LiBH4-ZrCl4|LLZTO-4LiBH4|22LiBH4-ZrCl4 prepared in Example 2 and LLZTO-4LiBH4|22LiBH4-ZrCl4|LLZTO-4LiBH4 prepared in Ratio 2. Due to the rapid lithium ion conductivity of this type of material, only one straight line is finally presented in the EIS graph. According to the spectrum, at 30°C, the impedance of 22LiBH4-ZrCl4|LLZTO-4LiBH4|22LiBH4-ZrCl4 is R=8112Ω, and the impedance of LLZTO-4LiBH4|22LiBH4-ZrCl4|LLZTO-4LiBH4 is R=8173Ω. According to the formula σ Li+ =d / SR, the calculated lithium ion conductivity is 1.569×10 -5 S / cm and 1.558×10 -5 There is no significant difference in the ionic conductivity of the two, and placing the lithium-stable borohydride-based electrolyte on both sides achieves high ionic conductivity without significantly reducing the conductivity of the composite solid electrolyte.

[0086] like Fig.10 As shown, the DC polarization curves (DC) of the composite electrolyte material 22LiBH4-ZrCl4|LLZTO-4LiBH4|22LiBH4-ZrCl4 prepared in Example 2 and LLZTO-4LiBH4|22LiBH4-ZrCl4|LLZTO-4LiBH4 prepared in Ratio 2 are shown. At 30°C, the measured voltage U0=0.1V, and the final steady-state current I0 are 8.7×10 -9 A and 4.0×10 -9 A, according to the electronic conductivity calculation formula σ e- =I0d / U0S, the final calculation can get the electronic conductivity σ e- They are 2.215×10 -8 S / cm and 1.019×10 -8 S / cm is 3 orders of magnitude smaller than the ionic conductivity and can be ignored.

[0087] like Fig.11 The following is a critical current density (CCD) test curve of the composite electrolyte material LLZTO-22LiBH4-ZrCl4 prepared in Comparative Example 11. At room temperature 25°C, the critical current density of the composite electrolyte is less than 0.7 mA / cm 2, indicating that the direct physical mixing of oxide-based electrolytes and borohydride electrolytes results in a composite electrolyte with poor stability to lithium and is unable to take advantage of the borohydride's strong ability to resist lithium dendrite growth, further demonstrating the technological advancement of the composite electrolyte with a multilayer structure design.

[0088] like Fig.12 As shown, it is the electrochemical impedance spectrum (EIS) of the composite electrolyte material LLZTO-22LiBH4-ZrCl4 prepared in Comparative Example 11. According to the spectrum, the impedance R of LLZTO-22LiBH4-ZrCl4 at 30°C is 14080Ω. According to the formula σ Li+ =d / SR, the calculated lithium ion conductivity is 8.1x10 -6 Compared with the multilayer composite solid electrolyte, the lithium ion conductivity of the obtained oxide and borohydride mixed composite electrolyte is significantly reduced, which further reflects the technical advancement of the multilayer structure design composite electrolyte of the embodiment.

[0089] like Fig.13 The following is a critical current density (CCD) test curve of the composite electrolyte material Li3InCl6-22LiBH4-ZrCl4 prepared in Comparative Example 12. At room temperature 25°C, the critical current density of the composite electrolyte is less than 0.1 mA / cm 2 , indicating that the direct mixing of halide electrolyte and borohydride electrolyte will result in a composite electrolyte with weak resistance to lithium dendrite growth, and cannot give full play to the advantages of borohydride electrolyte to achieve a high critical current density.

[0090] like Fig.14 As shown, it is the electrochemical impedance spectrum (EIS) of the composite electrolyte material Li3InCl6-22LiBH4-ZrCl4 prepared in Comparative Example 12. According to the spectrum, the impedance R of Li3InCl6-22LiBH4-ZrCl4 at 30°C is 1818Ω. According to the formula σ Li+ =d / SR, the calculated lithium ion conductivity is 6.3x10 -5 S / cm. Compared with the multilayer composite solid electrolyte, the lithium ion conductivity of the obtained halide and borohydride mixed composite electrolyte is significantly reduced, and the advantage of high lithium ion conductivity of the halide electrolyte is not brought into play, which further reflects the technical advancement of the multilayer structure design composite electrolyte.

[0091] Application Example 1

[0092] The multilayer composite solid electrolyte sheet 22LiBH4-ZrCl4|Li3InCl6|22LiBH4-ZrCl4 prepared in Example 1 was then ground and mixed with commercial LiCoO2 and 22LiBH4-ZrCl4 in a mass ratio of 4:6 in a mortar for 5 minutes to obtain a composite positive electrode for an all-solid-state battery. 10 mg of the composite positive electrode was placed on the 22LiBH4-ZrCl4|Li3InCl6|22LiBH4-ZrCl4 composite electrolyte sheet and pressed into a sheet at a pressure of 450 MPa for 5 minutes. Finally, a lithium metal sheet with a diameter of 1 cm was placed on the other side as a negative electrode, and the whole was kept at a pressure of 125 MPa for 5 minutes to obtain a Li / 22LiBH4-ZrCl4|Li3InCl6|22LiBH4-ZrCl4 / LiCoO2 all-solid-state battery.

[0093] like Fig.15 The figure shows the cycle performance of the Li / 22LiBH4-ZrCl4|Li3InCl6|22LiBH4-ZrCl4 / LiCoO2 all-solid-state battery at room temperature in Application Example 1. At a rate of 0.5C, the assembled full battery can still maintain a high capacity and cycle stably, indicating that the multilayer composite solid electrolyte has good lithium ion transport performance and lithium stability.

[0094] Application Example 2

[0095] The multilayer composite solid electrolyte sheet 22LiBH4-ZrCl4|Li3InCl6|22LiBH4-ZrCl4 prepared in Example 1 was then ground and mixed with commercial TiS2 and 22LiBH4-ZrCl4 at a mass ratio of 4:6 for 5 minutes to obtain a composite positive electrode. 10 mg of the composite positive electrode was placed on the 22LiBH4-ZrCl4|Li3InCl6|22LiBH4-ZrCl4 composite electrolyte sheet and pressed into a sheet at a pressure of 450 MPa for 5 minutes. Finally, a lithium metal sheet with a diameter of 1 cm was placed on the other side as a negative electrode, and the whole was kept under a pressure of 125 MPa for 5 minutes to obtain a Li / 22LiBH4-ZrCl4|Li3InCl6|22LiBH4-ZrCl4 / TiS2 all-solid-state battery.

[0096] Application Example 3

[0097] The multilayer composite solid electrolyte sheet 22LiBH4-ZrCl4|LLZTO-4LiBH4|-22LiBH4-ZrCl4 prepared in Example 2 was then ground and mixed with commercial LiCoO2 and 22LiBH4-ZrCl4 at a mass ratio of 4:6 for 5 minutes to obtain a composite positive electrode. 10 mg of the composite positive electrode was placed on the 22LiBH4-ZrCl4|LLZTO-4LiBH4|-22LiBH4-ZrCl4 composite electrolyte sheet and pressed into a sheet at a pressure of 450 MPa for 5 minutes. Finally, a lithium metal sheet with a diameter of 1 cm was placed on the other side as a negative electrode, and the whole was kept at a pressure of 125 MPa for 5 minutes to obtain a Li / 22LiBH4-ZrCl4|LLZTO-4LiBH4|-22LiBH4-ZrCl4 / LiCoO2 all-solid-state battery.

Claims

1. A fast-chargeable multilayer composite solid electrolyte, characterized in that: It includes an intermediate layer and composite layers laminated on both sides of the intermediate layer. The intermediate layer is a high ionic conductivity electrolyte, and the composite layer is a high critical current density solid electrolyte.

2. The fast-chargeable multilayer composite solid electrolyte according to claim 1, characterized in that: The high ionic conductivity electrolyte is one or more of an oxide electrolyte, a halide electrolyte, and a sulfide electrolyte.

3. The fast-chargeable multilayer composite solid electrolyte according to claim 2, characterized in that: The oxide electrolyte includes Li 7-x A y La 3-y Zr 2-x M x O 12 And a composite solid electrolyte, wherein A is one of Mg, Ca, S, Ba, Nb, Ta, M is one of Ta, Nb, Hf, Al, Si, Ga, Ge, Sc, Ti, V, Y, Sn, 0≤x≤1, 0≤y≤1; the halide electrolyte includes Li 3-n D 1-n Zr n X6 and its modified solid electrolyte, wherein D is one of Y, Er, In, X is one of Cl, Br, 0≤n≤1; the sulfide electrolyte includes Li3PS4, Li7P3S 11 , Li 10 GeP2S 12 , Li (6-i) PS (5-i) E (1+i) , jLi2S·(1-j)P2S5 and modified electrolytes thereof, wherein E is one of Cl, Br, I, 0≤i≤0.6, 0.2≤j≤0.

8.

4. The fast-chargeable multilayer composite solid electrolyte according to claim 3, characterized in that: The high ionic conductivity electrolyte is Li 6.4 LqCy 1.4 Ta 0.6 O 12 One or more of the composite electrolyte LLZTO-4LiBH4 of (LLZTO) and LiBH4, the halide electrolyte Li3InCl6, and the sulfide electrolyte Li6PS5Cl.

5. The fast-chargeable multilayer composite solid electrolyte according to claim 1, characterized in that: The high critical current density solid electrolyte includes one or more of composite LiBH4-based solid electrolytes LiBH4-ZrCl4, LiBH4-TiCl4, LiBH4-ZrI4, LiBH4-TiI4, LiBH4-HfCl4, LiBH4-HfI4, LiBH4-YCl4, LiBH4-TaCl5, and LiBH4-LaCl3.

6. The fast-chargeable multilayer composite solid electrolyte according to claim 5, characterized in that: The high critical current density solid electrolyte is the composite LiBH4-based solid electrolyte LiBH4-ZrCl4.

7. A method for preparing a fast-chargeable multilayer composite solid electrolyte, characterized in that: It includes the following steps: Step 1: In a glove box under an argon atmosphere, weigh a quantitative amount of high ionic conductivity electrolyte powder into a stainless steel mold, and use a hydraulic press to press the powder into a high ionic conductivity electrolyte sheet. Step 2: Weigh a quantitative amount of high critical current density solid electrolyte powder respectively and composite it on both sides of the high ionic conductivity electrolyte sheet to form a sandwich-style multi-layer composite solid electrolyte sheet.

8. The method for preparing the fast-chargeable multilayer composite solid electrolyte according to claim 7, characterized in that: The composite method in Step 2 is: Set a quantitative amount of high critical current density solid electrolyte powder on both sides of the high ionic conductivity electrolyte sheet, and use a hydraulic press to press to form a sandwich-style multi-layer composite solid electrolyte sheet; wherein, the mass ratio of the high ionic conductivity electrolyte powder to the high critical current density solid electrolyte powder is m:1 - m, where 0 < m < 1; the pressure of the hydraulic press or roll press acting on the intermediate layer is 60 - 125 MPa; the pressure of the hydraulic press or roll press acting on the sandwich-style multi-layer composite solid electrolyte sheet is 150 - 450 MPa.

9. The method for preparing a fast-chargeable multilayer composite solid electrolyte according to claim 7, characterized in that: The composite method in Step 2 is: In-situ polymerize a quantitative amount of high critical current density solid electrolyte powder on both sides of the high ionic conductivity electrolyte sheet. The in-situ polymerization includes dispersing and mixing an electrolyte, a small molecule monomer, an adhesive, and a polymerization initiator in a solvent according to a set ratio to form a slurry, coating the slurry on both sides of the high ionic conductivity electrolyte sheet, and drying to remove the solvent; wherein, the small molecule monomer includes one or more mixtures of ethoxylated trimethylolpropane triacrylate, cyclic carbonate, vinylene carbonate, diallyl carbonate, ethylene glycol dimethacrylate, ethylene sulfite vinyl ester, fluoro vinylene carbonate, vinyl acetate, 1,3-propylene sulfonic acid lactone, ethylene ethyl carbonate, maleimide compounds, maleamide compounds, maleic anhydride compounds, methyl vinyl sulfone, ethyl vinyl sulfone, methyl methacrylate, butyl acrylate, and acrylamide.

10. Application of a fast-chargeable multi-layer composite solid electrolyte in an all-solid-state lithium-ion battery, characterized in that: Assemble the fast-chargeable multi-layer composite solid electrolyte with a positive electrode material and a negative electrode material into an all-solid-state battery.